The republic of hunger and other essays - Patnaik, Utsa (Three Essays Collective, 2007)
Utsa Patnaik’s book is as much a comment on the state of economics as a discipline today, as on the economic policies that are ruining the lives and livelihoods of millions of people in the Third World. The unifying theme of her essays is the impact on the Third World of the new imperialism in the present era, which takes the form of deflationary neo-liberal ‘economic reforms’, a thrust towards free trade and subservient agriculture. She shows how these policies are causing unprecedented rural distress and universal hunger in the developing countries including India. Hers is a voice of sanity, conscience and true scholarship. UTSA PATNAIK UTSA PATNAIK retired as Professor of Economics at the Centre for Economic Studies and Planning, Jawaharlal Nehru University, New Delhi. She has written extensively on political economy, capitalism and the agrarian question. She is the author of The Long Transition: Essays on Political Economy (1999), and The Republic of Hunger and Other Essays (2007), and has edited two volumes of The Agrarian Question in Marx and his Successors for LeftWord Books.